Occurrence of lymphadenitis in swine created in conventional and deep-litter system at the growth-termination phase (Revista de Ciências Agroveterinárias, 2006)
The occurrence of granulomatous lymphadenitis caused by the agents of the Mycobacterium avium Complex (MAC), and other pathologies, was studied comparing pigs created in deep-litter with two substrates. The study used 72 pigs/treatment/group in four consecutive groups distributed in three treatments: T1 deep-litter of wood shaving, T2 deeplitter of rice husk and T3 partially slatted floor. In all three treatments 2 pigs/pen at the first group were challenged with 2mg of MAC inoculum, in the first day. The occurrence of lymphadenitis was greater in pigs created in wood shaving, followed by those in rice husk and those in conventional system. The percentage of rough fiber in the feces was higher on animals grown in wood shaving, followed by those in rice husk, showing differences between treatments. This indicates that pigs ingested the materials used as bedding. The daily gain and conversion feed were better in pigs created in conventional system.
Keywords: swine; Mycobacterium avium; pneumonia; atrophic rhiniti.